2014
DOI: 10.1039/c4ra01967a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective intramolecular aldol ring closures of threonine derivatives leading to densely functionalised pyroglutamates related to oxazolomycin

Abstract: Intramolecular aldol reactions on oxazolidine templates derived from threonine may be used to generate libraries of densely functionalised pyroglutamates with a high level of diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…The stereochemistry of the newly created stereogenic centre for the major diastereomer was established as 7R (that is, hydroxyl group endo) by NOE analysis (Figure 1), and the stereochemistry of the others was assumed by the similarity of chemical shift values of H-6 exo and H-6 endo with this NOE-assigned structure (H-6 = 3.04 and 2.45 ppm for 7a). This was similar to reported chemical shifts of the H-6 protons for the serine (H-6 endo ( = 3.2 ppm) and H-6 exo ( = 2.5 ppm) 3 ) and threonine (H-6 exo ( = 3.1 ppm) and H-6 endo ( = 2.4 ppm) 6 ). This earlier work had shown those chemical shifts were conserved in similar diastereomers, generally regardless of substitution, and in the systems reported here, the chemical shift values for H-1 H. Almahli et al…”
Section: Letter Syn Lettsupporting
confidence: 89%
See 3 more Smart Citations
“…The stereochemistry of the newly created stereogenic centre for the major diastereomer was established as 7R (that is, hydroxyl group endo) by NOE analysis (Figure 1), and the stereochemistry of the others was assumed by the similarity of chemical shift values of H-6 exo and H-6 endo with this NOE-assigned structure (H-6 = 3.04 and 2.45 ppm for 7a). This was similar to reported chemical shifts of the H-6 protons for the serine (H-6 endo ( = 3.2 ppm) and H-6 exo ( = 2.5 ppm) 3 ) and threonine (H-6 exo ( = 3.1 ppm) and H-6 endo ( = 2.4 ppm) 6 ). This earlier work had shown those chemical shifts were conserved in similar diastereomers, generally regardless of substitution, and in the systems reported here, the chemical shift values for H-1 H. Almahli et al…”
Section: Letter Syn Lettsupporting
confidence: 89%
“…(Scheme 2); 5,6 coupling of these with thiazolidines 4a-e gave acetoacetylthiazolidines 6a-m in good yield (Scheme 2 and Table 2). These compounds existed as rotamers in several cases, as evidenced by broad signals in the 1 H NMR spectrum, as keto-enol mixtures, and as a mixture of diastereomers, leading to complex NMR spectra, but were nonetheless used directly for further reaction.…”
Section: Letter Syn Lettmentioning
confidence: 99%
See 2 more Smart Citations
“…71 We wondered if we could apply the elegant 'Self-Regeneration of Stereocenters' concept of Seebach 72 in an intramolecular manner, and found that highly functionalised pyroglutamates 48a were directly available by diastereoselective aldol ring closures of ketoacyloxazolidines 47a derived from serine 46a. 73 This reaction also later proved to be suitable for threonine-derived oxazolidine 47b 74,75 and cysteine-derived thiazolidine 47c templates giving pyroglutamates 48b,c (Scheme 5), 76,77 although these aldol reactions may be reversible. 78 Similar stereoselective intramolecular aldol reactions of (4R)-3-(3oxobutanoyl)-1,3-thiazolidine-4-carboxylates have been reported and are believed to be directed by 'self-induced' axial chirality.…”
Section: Synthesised By Construction Of a New Ringmentioning
confidence: 99%